1997
DOI: 10.1136/bmj.315.7108.576
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of compression treatment for venous leg ulcers

Abstract: Objective: To estimate the clinical and cost effectiveness of compression systems for treating venous leg ulcers. Methods: Systematic review of research. Search of 19 electronic databases including Medline, CINAHL, and Embase. Relevant journals and conference proceedings were hand searched and experts were consulted. Main outcome measures: Rate of healing and proportion of ulcers healed within a time period. Study selection: Randomised controlled trials, published or unpublished, with no restriction on date or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
2
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(191 citation statements)
references
References 13 publications
(9 reference statements)
2
182
2
5
Order By: Relevance
“…Compression therapy within the setup of a leg ulcer clinic is widely recognised as the main modality for managing venous leg ulcers [17,18,51,52]. A previous study mentioned that contemporary dressing materials do not stimulate healing, and expenses are not clinically justified as they have no proven efficacy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Compression therapy within the setup of a leg ulcer clinic is widely recognised as the main modality for managing venous leg ulcers [17,18,51,52]. A previous study mentioned that contemporary dressing materials do not stimulate healing, and expenses are not clinically justified as they have no proven efficacy [19].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review 35 (updated by Cullum and colleagues 31 ) concluded that patients with venous leg ulcers who receive compression therapy are ; however, these trials involved only 328 patients in total, and therefore even taken together they lacked power to detect clinically important differences in leg ulcer healing.…”
Section: Clinical Effectiveness Of Different Bandage Systemsmentioning
confidence: 99%
“…Because of the methodological weaknesses of studies identified in the review by Fletcher and colleagues 35 we felt that a study that examined the clinical and cost-effectiveness of different compression systems was justified.…”
Section: Background To Venous Ulcer Study (Venus) Trialmentioning
confidence: 99%
“…Medical hosiery is a useful and convenient method of applying a graduated compression to prevent the development or recurrence of leg ulcers. Compression bandages currently represent the treatment of choice [9,10]. However, hosiery and compression bandages are of limited value in the treatment of active ulceration, difficult to apply over dressings, tend to lose mechanical strength and stiffness due to breakdown of fibres involved [11], and are expensive [12].…”
Section: Introductionmentioning
confidence: 99%